Development of AR Pocket Book with TaRL Approach in Geometry - Pertiwi, Putri Persada; Mas’ula, Siti; Yuniawatika, Yuniawatika (Angstrom Centre of Education, 2025)
This development is motivated by the needs of schools which require comparative teaching materials that can overcome the monotonous learning of spatial structures. This development aims to produce a pocket book based on Augemented Reality (AR) with a TaRL approach to improve student's mathematical problem solving abilities that are valid, practical and effective. This research method is Research and Development (R&D) with the ADDIE research model, namely analyze, design, development, implementation and evaluation. The instruments used are an expert validation questionnaire sheet, a teacher practicality questionnaire sheet, a student practicality questionnaire sheet, and a test of students' mathematical problem solving abilities. The results of the research show that the quality of this pocket book meets validity with an average score of 95.15% in the “very valid” category, meets practicality by teachers with an average score of 89% and practicality by students with an average score of 91.1% in the “very practical” category. Meanwhile, the test results meet the “effective” category with an average score of 0.8 with high criteria. It can be concluded that pocket book based on AR with the TaRL approach meets the criteria of being valid, practical and effective so that it can be used in learning.